Review of The Effectiveness of Plant Media Extracts in Barium Hexaferrite Magnets (BaFe12O19) - Jaya Edianta; Nanang Fauzi; Marzuki Naibaho; Fitri Suryani Arsyad; Idha Royani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Betel leaf is a typical Indonesian herbal plant that propagates on other tree trunks. So far, betel leaf has only been used in biomedicine and traditional medicine, whereas the chemical compounds of betel leaf can be used to absorb electromagnetic waves. In this mini-review, we review several research results to discuss the potential effectiveness of betel leaf in barium hexaferrite as an absorber of electromagnetic radiation. We compiled this mini-review based on the literature review method that is discussed extensively and in-depth regarding the chemical composition of betel leaf, modification of the development of barium hexaferrite material with betel leaf media extract, characteristics of BaFe12O19 as absorption of electromagnetic waves, and the effectiveness of media extracts in BaFe12O19 as absorption of electromagnetic waves. Based on the results of the literature review, the modification of BaFe12O19 material synthesis can include microemulsion, solid-state, coprecipitation, sol-gel, and hydrothermal synthesis. So far, hydrothermal synthesis is a synthesis method of mixing betel leaf extract media and ferrite-based magnets that have been studied before. Betel leaf in ferrite-based magnetic materials has been studied not to damage the surface morphology and characteristics of the magnetic material. The results of the assessment also show the effectiveness of adding other elements or compounds such as Ni, Al2O3, and composites in ferrite-based magnetic materials that can absorb more than 90% of electromagnetic waves in the frequency range 2-18 GHz.